Kalimat Metaforis Sebagai Sarana Estetika dalam Lirik Lagu nDangdut - Muhamad Hermintoyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Abstract In providing an aesthetic element, the lyricist will express it through poetic diction. In the hands of creative lyric writers, a figurative language will emerge. Metaphorical lyrics understanding does not have to have the same meaning that is written. Poetic language / poetic lyrics, the words can mean the meaning depends on the listener's understanding. Even so in the song nDangdut. In general, the song Dangdut tends to have a theme of love compared to other themes. This article discusses metaphorical diction as an aesthetic means. Meaning of metaphorical diction using hermeneutical reading. Keywords: diction, metaphor, hermeunetic, lyrics, dangdut